Coupling to a glioblastoma‐directed antibody potentiates antitumor activity of curcumin. Issue 3 (2nd April 2014) - Langone, Phyllis; Debata, Priya Ranjan; Inigo, Joseph Del Rosario; Dolai, Sukanta; Mukherjee, Sumit; Halat, Peter; Mastroianni, Kristina; Curcio, Gina Marie; Castellanos, Mario R.; Raja, Krishnaswami; Banerjee, Probal
<x xml:space="preserve">Abstract</x> Current therapies for glioblastoma are largely palliative, involving surgical resection followed by chemotherapy and radiation therapy, which yield serious side effects and very rarely produce complete recovery. Curcumin, a food component, blocked brain tumor formation but failed to eliminate established brain tumors in vivo, probably because of its poor bioavailability. In the glioblastoma GL261 cells, it suppressed the tumor‐promoting proteins NF‐κB, P‐Akt1, vascular endothelial growth factor, cyclin D1 and BClXL and triggered cell death. Expression of exogenous p50 and p65 subunits of NF‐κB conferred partial protection on transfected GL261 cells against curcumin insult, indicating that NF‐κB played a key role in protecting glioblastoma cells. To enhance delivery, we coupled curcumin to the glioblastoma‐specific CD68 antibody in a releasable form. This resulted in a 120‐fold increase in its efficacy to eliminate GL261 cells. A very similar dose response was also obtained with human glioblastoma lines T98G and U87MG. GL261‐implanted mice receiving intratumor infusions of the curcumin‐CD68 adduct followed by tail‐vein injections of solubilized curcumin displayed a fourfold to fivefold reduction in brain tumor load, survived longer, and about 10% of them lived beyond 100 days. Hematoxylin–eosin staining of brain sections revealed a small scar tissue mass in the rescued mice, indicating adduct‐mediated elimination of glioblastoma tumor. The tumor cells were strongly CD68+ and some cells in the tumor periphery were strongly positive for microglial Iba1, but weakly positive for CD68. This strategy of antibody targeting of curcumin to tumor comes with the promise of yielding a highly effective therapy for glioblastoma brain tumors.